Performance of shoulders adjacent to concrete pavements: final report to the Wisconsin Highway Research Program - Owusu-Ababio, Samuel; Schmitt, Robert (Wisconsin Highway Research Program, 2003)
The Wisconsin Department of Transportation (WisDOT) maintenance staff in both the Districts and Central Office discussed the less-than-optimum performance of the current asphalt shoulder design and standard being constructed adjacent to mainline concrete pavement projects. Problems associated with heaving of the shoulders during cold weather make snow removal operations more difficult and cause uneven wear on plow blades. Excessive cracking in both the longitudinal and transverse directions force maintenance crews to address these shoulders early in their life. In many cases, this is forcing continual maintenance crew exposure to high volume traffic roadways that are unwanted. This report presents a set of guidelines for consideration in paved shoulder practice in Wisconsin. The set of guidelines was developed through a series of tasks including: a) review and synthesis of literature on paved shoulders, b) survey of seven Midwestern states (Illinois, Indiana, Iowa, Ohio, Michigan, Minnesota and Wisconsin) regarding their shoulder practices, and c) data collection and analysis of in-service paved shoulders adjacent to mainline concrete pavements in Wisconsin. On the basis of the analysis several recommendations are made regarding the design elements for two feasible shoulder alternatives to minimize the extent and/or severity of specific key distresses. The two feasible shoulder alternatives are a) Jointed plain concrete shoulder tied to the mainline concrete pavement and b) a composite shoulder (an extended PCC width beyond the white line plus a specified asphalt-surfaced width). In addition, recommendations are made regarding elements for consideration in the effective management of shoulders.
266 p.
Keywords: Road shoulders; Transverse cracking; Recommendations; Surveys; Guidelines; Concrete pavements; Longitudinal cracking; Paved shoulders; Literature reviews; Data collection; Heaving